The judges in the democracy of the constitutional State - Cárdenas-Rivera, Miguel Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Thispaper isabout Liberalismin Colombia.Themainargument isthat throughout the whole twentieth century, Liberalism in Colombia failed to implement the social reformsthat it had promised as earlyas inthe thirties. Especiallyimportant was the failure of the agrarian social reform, which fed the further rise of the insurgent forces. Later on, in the nineties, Liberalism matured into a new form: Neoliberalism. This new form of Liberalism was less capable of producing the social reforms that the old Liberals had promised. Today, and after the historical development that the internal armed conflict in Colombia has followed, it is impossible to think that a return to the reformist Liberal path of the old times would be sufficient to provide a solution to the crisis in Colombia. Colombian Liberalism was simply not able to provide an organic and material base that would guide publicpolicies towards a fair distribution of wealth. And so, as this paper attempts to demonstrate that the Colombian war is a catastrophe that has its foundations in the failure of Colombian Liberalism.